PENGARUH MEDIA WORDWALL TERHADAP HASIL BELAJAR IPAS MATERI MENGENAL PERMUKAAN BUMI KELAS V SEKOLAH DASAR GUGUS IV CANDI KALASAN KECAMATAN BENDOSARI KABUPATEN SUKOHARJO TAHUN PELAJARAN 2025/2026 - Alfinna Rohmatu Rosyidah; Sri Mulyati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study was to determine the effect of Wordwall media on the learning outcomes of Grade V elementary school students in Gugus IV Candi Kalasan, Bendosari District, Sukoharjo Regency, in the 2025/2026 academic year, specifically in the subject of Earth Science, with the topic of understanding the Earth's surface. Data collection methods included tests and documentation. The population in this study was Cluster IV Candi Kalasan Elementary Schools, which consisted of six schools. This study was quantitative in nature and used an experimental method. Before the treatment was administered, the instruments were tested on the experimental group to determine the group's condition before the treatment. After the treatment, the experimental group and the control group were given a post-test to determine the condition of the groups. The sampling technique in this study used Cluster Random Sampling, with Mertan 03 Public Elementary School as the experimental class and Mertan 01 Public Elementary School as the control class. The data analysis technique used the t-test, after first conducting normality and homogeneity tests. The results based on the independent sample t-test obtained a Sig. (2-tailed) value of 0.00 < 0.05, so it can be concluded that there is an effect of the wordwall media on the learning outcomes of students in IPAS material on understanding the earth's surface at elementary schools in cluster IV Candi Kalasan, Bendosari District, Sukoharjo Regency, in the 2025/2026 academic year.